For everything there is a season: more than a year of destruction at Seleucid Tell Iẓṭabba (Israel). (October 2022) - Lichtenberger, Achim; Mienis, Henk; Orendi, Andrea; Pines, Miriam; Rittner, Oz; Tal, Oren
Abstract: Abstract : The Seleucid town of Nysa-Scythopolis on Tell Iẓṭabba (Israel) was destroyed by the Hasmoneans at the end of the second century BC. In this article, we discuss the exact season and possible year of the destruction using a multimodal approach and argue for its destruction in spring/early summer 107 BC.